Pandemic as a litmus test for the grand theories of European integration - Lovec, Marko (Teorija in praksa, 2020)
Several crises over the past decade have shown the inability of the European integration to reconcile the dysfunctionalities associated with the partial transfer of authorities to the transnational level and attracted criticism of the alleged pro-integration bias of the grand theories neofunctionalism, liberal governmentalism and postfunctionalism. This article takes as a case study the Covid-19 pandemic as a "moment of truth" that shares many aspects with past crises. It argues that, by addressing various dimensions of the demand for and supply of the integration, the three liberal institutional theories explain the nationalist response to the health crisis (missing demand and supply) and the integrationist decision on economic recovery (sufficient demand and supply). Moreover, they do this better than the nationalist or federalist approaches that either understate the demand for (the former) or overstate the supply of the integration (the latter).
Keywords: Covid-19; Crises; Economic policy; Ekonomska politika; Epidemics; Epidemije; evropska integracija; Evropska unija; Integracijski procesi; Krize; Process of integration; protikrizni ukrepi; velike teorije